POLICY ADVICE ON EQUAL ACCESS TO HEALTHCARE: WHAT'S NEW? - Muhlis, Abdu Nafan Aisul (Universitas Airlangga, 2024)
We have less than ten years to achieve the 2030 Sustainable Development Goals (SDGs). In the health sector, it is crucial to focus on Goal 3, which aims for the health and well-being of everyone. Despite progress, disparities in healthcare access continue to affect vulnerable populations. Some countries have implemented Universal Health Coverage (UHC) to ensure equal healthcare access. This editorial emphasized the need for targeted interventions, policy reforms, and increased public awareness to achieve equitable healthcare access and better health outcomes for diverse populations. Keywords: disparities, policy reforms, SDGs, UHC